Relação entre os princípios básicos de liderança e desempenho operacional: estudo com gestores e colaboradores de centros de distribuição domiciliar dos Correios, Regional Bahia - Tejerizo, Élida Morais (2011)
We cannot deny the constant challenges and tensions caused by the current organizational architectures, this is, based on the organizational power more diluted than before; in the increase of the manpower knowledge, making it more questioning; in the complexity, fragmentation and uncertainty of the manager's role and his/her responsibility for the results of the organization, among other no less important factors. This study aims at investigating the relationship between the basic principles of leadership by Posner and Kouzes (2008) to the operational performance. In other words, verify to what extent these principles impact on the results of the surveyed units. Thus, the survey was carried out in nineteen Home Distribution Centers within the capital and the countryside, within a universe of thirty-seven, thus reaching 50% of the studied group. The field research took place from September 2010 to May 2011. The survey form was developed and tested with employees of some units and then validated. The data was filled by the respondents themselves, under the guidance of the researcher. The methodology used was quantitative applied to the Postmen (employees) and their respective managers. Initially, the sample was of the non-probabilistic intentional kind and, after, for convenience. In total 559 questionnaires were validated. The study results indicate that there was no significant influence in a positive or negative way of the operating performance rates in any of the five studied principles (Challenge the process, Inspire a shared vision, Enable others to act, Delineate the way and Encouraging the Heart). In other words, there was no relationship between the basic principles of leadership to the operational performance.